The New Testament as canon : a reader in canonical criticism - Wall, Robert W. (Journal for the study of the New Testament. Supplement series, 1992)
This wide-ranging collection of essays provides the reader with a critical introduction to the New Testament as the church's canon. The authors' conviction is that the Bible belongs first of all to the community of believers rather than to the guild of biblical scholars. But that does not make the tools and tasks of modern biblical criticism unimportant. Rather, they are the constructive means by which the scholar discerns the nature of the ongoing conversation between the church and its biblical canon and helps form the church into a community of worship and witness. Whether from a particular.